Foreword - Gabrielle Appleby; Alexander Reilly; Sean Brennan (Legal Education Review)
In a company law course, the face-to-face lecture was flipped with the purpose of improving the lecture experience of students and their preparedness to engage in deep-learning seminar activities after the lecture. The flipped lecture consisted of a bundle of three tasks: a set of three pre-recorded videos narrating the lecture slides, an online graded quiz, and an oral feedback session on the quiz’s solutions. The students completed the first two tasks outside class but the third task in class. Data from a student survey and course grades were used to evaluate the performance of the flipped lecture compared with the face-to-face lecture. Although the results showed that, on average, there was only a slight difference in students’ preference and preparedness in favour of the flipped lecture, this difference turned out to be larger in magnitude and statistically significant when the sample was split by student GPA scores. The flipped lecture yielded greater benefits to Low-GPA students, compared with High-GPA students, especially when Low-GPA students watched the pre-recorded videos at least twice. Findings suggest that the group of students who need greater support in learning are the more likely to enjoy and profit from the flipped lecture.